Exchange Rate Determinants: Is Crude Palm Oil Price One of Them in Malaysia and Indonesia? - Azman Aziz, Mukhriz Izraf; Applanaidu, Shri Dewi (2016)
This paper studies the relationship between palm oil prices, Malaysia Ringgit and Indonesia Rupiah exchange rates using Dynamic OLS method. The paper employs unit root with structural break tests and Pesaran (2001) bound cointegration technique based on real monthly prices ranging 6om January 1983 to May 2015. The empirical results find negative and statistically significant evidence on the impact of real palm oil price changes on real exchange rates. The findings imply that increase in real palm oil price leads to real exchange rate appreciation.